Heme Oxygenase-1 as a Pharmacological Target for Host-Directed Therapy to Limit Tuberculosis Associated Immunopathology - Krishna C. Chinta; Hayden T. Pacl; Anupam Agarwal; Adrie J. C. Steyn (MDPI AG, 2021)
Excessive inflammation and tissue damage are pathological hallmarks of chronic pulmonary tuberculosis (TB). Despite decades of research, host regulation of these clinical consequences is poorly understood. A sustained effort has been made to understand the contribution of heme oxygenase-1 (HO-1) to this process. HO-1 is an essential cytoprotective enzyme in the host that controls inflammation and oxidative stress in many pathological conditions. While HO-1 levels are upregulated in animals and patients infected with Mycobacterium tuberculosis (Mtb), how it regulates host responses and disease pathology during TB remains unclear. This lack of clarity is due in part to contradictory studies arguing that HO-1 induction contributes to both host resistance as well as disease progression. In this review, we discuss these conflicting studies and the role of HO-1 in modulating myeloid cell functions during Mtb disease progression. We argue that HO-1 is a promising target for host-directed therapy to improve TB immunopathology.